FAKTOR PENDORONG ALIH USAHATANI JAGUNG KE USAHATANI NILAM DI DESA KOMBIKUNO KECAMATAN NAPANO KUSAMBI KABUPATEN MUNA BARAT - Munarti Munarti; Hartina Batoa; Awaluddin Hamzah (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
This study aims to determine the driving factors for the transfer of corn farming to patchouli farming in Kombikuno Village, Napano Kusambi District, West Muna Regency with a total of 25 informants. The method in this study uses qualitative analysis with the proposed by Miles and Huberman, namely data reduction, data presentation, and initial conclusions. The research results show that the motivating factor for the transfer of corn farming to patchouli farming in Kombikuno Village, Napano Kusambi District, West Muna Regency is influenced by two factors, namely technical factors (plant cultivation) including land management, maintenance, and post-harvest handling; and social factors include seeing the success of other farmers and following friends.